2003
DOI: 10.1242/dev.00375
|View full text |Cite
|
Sign up to set email alerts
|

bHLH transcription factor Her5 links patterning to regional inhibition of neurogenesis at the midbrain-hindbrain boundary

Abstract: The midbrain-hindbrain (MH) domain of the vertebrate embryonic neural plate displays a stereotypical profile of neuronal differentiation, organized around a neuron-free zone (`intervening zone', IZ) at the midbrain-hindbrain boundary(MHB). The mechanisms establishing this early pattern of neurogenesis are unknown. We demonstrate that the MHB is globally refractory to neurogenesis,and that forced neurogenesis in this area interferes with the continued expression of genes defining MHB identity. We further show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(110 citation statements)
references
References 70 publications
7
102
1
Order By: Relevance
“…Homozygous mutation of Tbx1 gene in mouse causes birth defects derived from developmental abnormalities of the embryonic pharyngeal sysIt has been shown that hairy controls the pattern of sensory organ formation by repressing achaete-scute (Orenic et al, 1993). In the zebrafish midbrain-hindbrain boundary, mouse olfactory placode and the inter-proneural stripes of Xenopus, Hairy and Enhancer of Split homologues (Hes/Her) repress neural fate (Cau et al, 2000, Geling et al, 2003, Bae et al, 2005. In chick otic cups, Hairy1 (Hes1 in mammals) is expressed restricted in the nonneural domain, disclosing a putative role in repressing proneural fate in the posterior region (Abelló et al, 2007).…”
Section: Model C: Successive Inductions and Repression Of Neural Fatementioning
confidence: 99%
“…Homozygous mutation of Tbx1 gene in mouse causes birth defects derived from developmental abnormalities of the embryonic pharyngeal sysIt has been shown that hairy controls the pattern of sensory organ formation by repressing achaete-scute (Orenic et al, 1993). In the zebrafish midbrain-hindbrain boundary, mouse olfactory placode and the inter-proneural stripes of Xenopus, Hairy and Enhancer of Split homologues (Hes/Her) repress neural fate (Cau et al, 2000, Geling et al, 2003, Bae et al, 2005. In chick otic cups, Hairy1 (Hes1 in mammals) is expressed restricted in the nonneural domain, disclosing a putative role in repressing proneural fate in the posterior region (Abelló et al, 2007).…”
Section: Model C: Successive Inductions and Repression Of Neural Fatementioning
confidence: 99%
“…Hes1 directly contributes to the promotion of progenitor cell proliferation through transcriptional repression of a cyclin-dependent kinase inhibitor, p27Kip1, in embryonic carcinoma cells (Murata et al, 2005). Zebrafish p27 xic1 expression is negatively regulated by Her5 in the midbrain-hindbrain boundary (Geling et al, 2003). These findings suggested that hes-related genes might be involved in maintaining neural crest stem cells in the mitotic and undifferentiated state.…”
Section: Introductionmentioning
confidence: 96%
“…For example, three neurogenic zones form along the dorsoventral axis of the spinal cord during primary neurogenesis due to inhibition of differentiation in the intervening regions by specific Hes/Her and Zic genes (Brewster et al, 1998;Bae et al, 2005). Similarly, a non-neurogenic zone forms at the midbrainhindbrain boundary due to the inhibitory action of Hes/Her family members (Geling et al, 2003;Geling et al, 2004). In these examples, the expression of transcription factors that inhibit neuronal differentiation appears to be linked to dorsoventral and anteroposterior patterning within the neural epithelium that underlies cell type and regional specification.…”
Section: Introductionmentioning
confidence: 99%